Development of snakes and ladders media to enhance grade IV Javanese reading and writing skills - Fara Zaitun Chusnullita; Deni Setiawan (Research and Development in Education (RaDEn), 2024)
Javanese language learning especially Javanese script material poses several challenges, so the utilization and implementation of concrete learning media is a promising solution to offer a more interactive learning experience and increase student success. The purpose of this project is to create, test the feasibility, and evaluate the efficacy of employing snake and ladder learning media. Javanese script material in elementary schools. The subjects of the study were 30 grade IV students of SDN 03 Jaten, Karanganyar, Central Java. Research and Development (R&D) uses the Borg and Gall model and collects data through observation, interviews, and tests. The feasibility results of material expert validation obtained a score of 94% which indicates the media is suitable for use and trial. Then the results of media expert validation showed a 93% gain with criteria worthy of trial according to the revision submitted.  The result of students' responses to snakes and ladders media was 94.5%. Pretest and posttest values were analyzed to get the normal category, followed by a t-test with a sig (2-tailed) value of 0.000 < 0.05. The use of Snakes and Ladders learning media is stated to have a significant effect on Javanese script material in elementary schools. The N-Gain score shows a mean value of 0.5213 which is included in the medium category. Based on the research objectives and problem formulation, it can be concluded that the development of the Snakes and Ladders learning media has an effect on the learning outcomes of class IV students on Javanese script material in accordance with the results of research that researchers have conducted.